2019
DOI: 10.1039/c8ra10123j
|View full text |Cite
|
Sign up to set email alerts
|

Stable global tubular boron clusters in Na2B18 and Na2B18

Abstract: The optimal electrostatic interactions arising from the doping effect play a crucial role in stabilizing the tubular structure against the planar and quasi-planar preferences of the negatively charged boron clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Tubular structures have also been reported for LiB 20 and LiB 20 − , 55 and Na 2 B 18 and Na 2 B 18 − clusters. 56 The electrostatic interaction between the Li/Na atoms and the boron cluster motif was found to be essential for the stability of these cage-type and tubular structures. Similarly, theoretical calculations revealed that Be, Mg and Al doped boron clusters form planar, quasi-planar and bowl like structures except for MgB 18 and BeB 18 /BeB 20 − which were reported to form tubular drum and cage-type clusters, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…Tubular structures have also been reported for LiB 20 and LiB 20 − , 55 and Na 2 B 18 and Na 2 B 18 − clusters. 56 The electrostatic interaction between the Li/Na atoms and the boron cluster motif was found to be essential for the stability of these cage-type and tubular structures. Similarly, theoretical calculations revealed that Be, Mg and Al doped boron clusters form planar, quasi-planar and bowl like structures except for MgB 18 and BeB 18 /BeB 20 − which were reported to form tubular drum and cage-type clusters, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…173 Dong et al also found it in B 18 Na 2 and B 18 Na 2 − . 193 They substituted Na with Li and K in the structures obtained from the PES exploration, which yielded the double-ring as the most stable species within this pool of isomers. In this sense, there is a considerable possibility that the GMs of Li 2 B 18 , Li 2 B 18 − , B 18 K 2 , and B 18 K 2 − have the tubular form.…”
Section: Introductionmentioning
confidence: 99%
“…So, the authors characterized these tubular clusters as “salt complexes”. 193 In addition, the AdNDP approach revealed three types of bonds. Eighteen 2c-2e σ-bonds are forming the two separate B monocycles, along with five 20c-2e σ-bonds and five 20c-2e π-bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, metal-doped small-sized boron clusters have been intensively studied, involving alkali, 8,32 alkaline earth, 6,30 and transition metal atom doping. 14,26,29,[33][34][35][36][37][38][39][40] For example, there are Li 2 B 12 , 41 Na 2 B 18 , 42 LiB 20 , 32 MgB n (n = 10-20), 43 17,50 In addition, the number of studies on light actinide(III) complexes reported so far is relatively limited. [51][52][53] If the B 7 3À boron ligand has the ability to stabilize low-valent actinides, it may provide a new way for the synthesis of lowvalent actinide complexes.…”
mentioning
confidence: 99%